2007
DOI: 10.4049/jimmunol.179.3.1524
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Dendritic Cells Present Parenchymal Self-Antigen and Contribute to, but Are Not Essential for, Tolerization of Naive and Th1 Effector CD4 Cells

Abstract: Bone marrow-derived APC are critical for both priming effector/memory T cell responses to pathogens and inducing peripheral tolerance in self-reactive T cells. In particular, dendritic cells (DC) can acquire peripheral self-Ags under steady state conditions and are thought to present them to cognate T cells in a default tolerogenic manner, whereas exposure to pathogen-associated inflammatory mediators during the acquisition of pathogen-derived Ags appears to reprogram DCs to prime effector and memory T cell fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
14
1
Order By: Relevance
“…Our data contrast with the two previous reports implicating anergy induction as a key tolerogenic mechanism for memory or effector CD4 1 T cells. One report indicates that resting, but not activated, B cells inactivate memory CD4 1 T cells through anergy induction [23], whereas the second report shows that DC may be dispensable and that the key mechanism is induction of anergy [29]. Comparison of these data with ours suggests that B cells or other non-DC tolerogenic APC induce anergy in memory CD4 1 T cells, whereas DC appear to induce both deletion and unresponsiveness.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Our data contrast with the two previous reports implicating anergy induction as a key tolerogenic mechanism for memory or effector CD4 1 T cells. One report indicates that resting, but not activated, B cells inactivate memory CD4 1 T cells through anergy induction [23], whereas the second report shows that DC may be dispensable and that the key mechanism is induction of anergy [29]. Comparison of these data with ours suggests that B cells or other non-DC tolerogenic APC induce anergy in memory CD4 1 T cells, whereas DC appear to induce both deletion and unresponsiveness.…”
Section: Discussionsupporting
confidence: 44%
“…40: 2016Immunol. -2025 Immunomodulation , whereas the second report shows that DC may be dispensable and that the key mechanism is induction of anergy [29]. Comparison of these data with ours suggests that B cells or other non-DC tolerogenic APC induce anergy in memory CD4 1 T cells, whereas DC appear to induce both deletion and unresponsiveness.…”
supporting
confidence: 60%
“…Tissue-specific or tumor antigens may be taken up by resting DCs and cross-presented, resulting in the tolerization of T cells (13)(14)(15). Furthermore, others have reported that pDCs residing in tumor may deliver poor or tolerogenic signals to T cells (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses cDC requirement for LCMV, 35 HSV-1, 36 VSV, 37 influenza, 38 CTL response cDC independence of anti-VSV B and CD4 T-cell response 36,39 Bacteria cDC requirement for anti-Listeria CTL response 11,40 cDC requirement for efficient Mycobacterium tuberculosis CD4 T-cell response 41 cDC requirement for anti-Salmonella response 42,43 cDC independence of UPEC clearance 44 Parasites cDC requirement for anti-Plasmodium 11 and anti-Leishmania response 45,46 Prions cDC requirement for intestinal Scrapie agent neuroinvasion 47 Miscellaneous Tolerance cDC role in Ig complex-mediated priming and tolerization 48,49 cDC independence of peripheral CD4 T-cell tolerization 50 NK responses cDC requirement for NK cell activation by IL-15 trans-presentation 25 NKT responses cDC requirement for glycolipid presentation 51,52 CTL responses cDC requirement for efficient CTL memory generation 27 Respiratory tract cDC requirement for asthma and experimental allergic rhinitis 18,53 Tumor studies cDC requirement for antitumor immunity 52 DC functions by conditional cell ablation A Sapoznikov and S Jung subpopulations and generally provided by non-hematopoietic cells, including stromal and follicular dendritic cells; 58 and (2) the chemokine macrophage migration inhibitory factor (MIF) that controls mature B-and tumor cell survival through triggering of the CD74-CD44 receptor complex. [59][60][61] 70 on pDC.…”
Section: Pathogen Defensementioning
confidence: 99%